Antimicrobial and Antibiofilm Activity of Mango Seeds Extract - Faroun Ahmed, Entissar (Iraqi Journal of Science, 2023)
Mango fruit is one of the most nutritionally rich fruits with unique flavor, this fruit belonged to family of Anacardiaceae and it is an excellent source of vitamins specially vitamin A, carotene pigments and potassium. In this study the antimicrobial activity of mango seeds extract has been investigated against gram positive bacteria (Staphylococcus aureus and Bacillus spp.) and gram negative bacteria (Pseudomonas aeruginosa and E. coli) and yeast Candida albicans by well diffusion method in nutrient agar and the results were expressed as the diameter of bacterial inhibition zones surrounding the wells, and the antibiofilm of its extracts was observed against Staphylococcus aureus. The seeds extractions prepared by two solvents: 85% ethanol and 85% acetone, also the minimum inhibition concentration values (MIC) was determined for the two extracts. Also the compounds of the mango seeds extracts were identified by using gas chromatography-mass spectrometry (GC-MS). The results showed that the ethanol mango seeds extraction more efficient than acetone extraction as the inhibition zones by ethanol extract ranging between 15mm – 27mm while by acetone extract between 12mm–25mm, the MIC for two solvents extracts was approximately at the concentration 125 μg/ml and the antibiofilm test showed the ethanol extract inhibited the bacterial adhesion on glass tube and that cause biofilm detachments on it in compare with control tubes more than acetone extract which showed low effect.